Development and Characterization of PLGA Nanoparticles Containing 17-DMAG, an Hsp90 Inhibitor - Cruz, Kercia P.; Patricio, Beatriz F. C.; Pires, Vinícius C.; Amorim, Marina F.; Pinho, Alan G. S. F.; Quadros, Helenita C.; Dantas, Diana A. S.; Chaves, Marcelo H. C.; Formiga, Fabio R.; Rocha, Helvécio V. A.; Veras, Patrícia S. T. (Frontiers in Chemistry, 2021)
Leishmaniasis is a spectrum of neglected tropical diseases. Cutaneous form (CL) is characterized by papillary or ulcerated skin lesions that negatively impact patients' quality of life. Current CL treatments suffer limitations, such as severe side effects and high cost, making the search for new therapeutic alternatives an imperative. In this context, heat shock protein 90 (Hsp90) could present a novel therapeutic target, as evidence suggests that Hsp90 inhibitors, such as 17-Dimethylaminoethylamino-17-Demethoxygeldanamycin (17-DMAG), may represent promising chemotherapeutic agents against CL. As innovative input for formulation development of 17-DMAG, nano-based drug delivery systems could provide controlled release, targeting properties and reduced drug toxicity. In this work, a double emulsion method was used to develop poly (lactic-co-glycolic acid) (PLGA) nanoparticles containing 17-DMAG. The nanoparticle was developed using two distinct protocols: Protocol 1 (P1) and Protocol 2 (P2), which differed concerning the organic solvent (acetone or dichloromethane, respectively) and procedure used to form double-emulsions (Ultra-Turrax® homogenization or sonication, respectively). The nanoparticles produced by P2 were comparatively smaller (305.5 vs. 489.0 nm) and more homogeneous in size (0.129 vs. 0.33) than the ones made by P1. Afterward, the P2 was optimized and the best composition consisted of 2 mg of 17-DMAG, 100 mg of PLGA, 5% of polyethylene glycol (PEG 8000), 1.5 mL of the internal aqueous phase, 1% of polyvinyl alcohol (PVA), and 4 mL of the organic phase. Optimized P2 nanoparticles had a particle size of 297.2 nm (288.6 – 304.1) and encapsulation efficacy of 19.35% (15.42 – 42.18) by the supernatant method and 31.60% (19.9 – 48.79) by the filter/column method. Release kinetics performed at 37 °C indicated that approximately 16% of the encapsulated 17-DMAG was released about to 72 h. In a separate set of experiments, a cell uptake assay employing confocal fluorescence microscopy revealed the internalization by macrophages of P2-optimized rhodamine B labeled nanoparticles at 6, 24, 48 and 72 h. Collectively, our results indicate the superior performance of P2 concerning the parameters used to assess nanoparticle development. Therefore, these findings warrant further research to evaluate optimized 17-DMAG-loaded nanoparticles (NP2-17-DMAG) for toxicity and antileishmanial effects in vitro and in vivo.